Upaya Meningkatkan Kemampuan Pemecahan Masalah Siswa Kelas VIII Dengan Model Pembelajaran Problem Based Learning (PBL) Berbantuan Geogebra Pada Materi Bangun Ruang - Sindi Sahela; Suci Frisnoiry (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is a Classroom Action Research (PTK) which is carried out in 2 cycles. Before carrying out research or taking action, an initial test is given to measure students' problem-solving ability and at the end of each cycle a problem-solving ability test is given. This study aims to determine how to improve problem solving skills through the application of the Geogebra-assisted Problem Based Learning (PBL) learning model. Students experienced an increase in problem-solving skills, in the initial test the average problem-solving ability was 42.19%. In the first cycle, the test results showed an increase of 57.81%. From the results of the second cycle test also increased to 88.50%. The test results showed an increase in students' problem-solving abilities. Thus, it can be concluded that the application of the Geogebra media-assisted PBL model can improve students' problem-solving abilities.